Acquiring antecedents for reflexives when both L1 and L2 permit long-distance binding. (1st August 2017) - Umeda, Mari; Takeda, Kazue; Hirakawa, Makiko; Fukuda, Michiko; Hirakawa, Yahiro; Matthews, John; Snape, Neal
The present study examines second language (L2) acquisition of the Japanese reflexive zibun (self) by Chinese-speaking learners. The reflexive zibun allows both local and long-distance (LD) binding interpretations. In a recent analysis, zibun is categorized into three types: zibun bound locally by a co-argument, zibun bound by an empathic LD antecedent, and zibun bound by a logophoric LD antecedent. An empathic antecedent is the participant in a sentence that the speaker most empathizes with, whereas, a logophoric antecedent is an individual "whose speech, thoughts, feelings, or general state of consciousness are reported" (Clements, 1975 ). Chinese also has a reflexive, ziji (self), that can be bound by an LD antecedent, like Japanese zibun . However, Chinese ziji is categorized into two (not three) types: locally bound ziji and ziji bound by a logophoric LD antecedent (Huang, Li & Li, 2009 ). The goal of this study is to determine whether Chinese-speaking learners are able to distinguish the two different types of LD antecedent for zibun in Japanese. Twenty-eight Chinese-speaking learners of Japanese at advanced levels of proficiency and 36 native speakers of Japanese participated in the study. The results showed that Chinese learners were unable to distinguish between the two types of LD antecedents, showing a persistent presence of first language (L1) transfer.